2005
DOI: 10.1002/dc.20181
|View full text |Cite
|
Sign up to set email alerts
|

Unusual finding in a nipple discharge of a female dog: Dirofilariasis of the breast

Abstract: We report a case of dirofilariasis of the breast occurring in a 6-yr-old Bernese female dog living in central Italy presenting with a breast lump, diagnosed on cytological examination of nipple secretion fluid smears. The direct smears of nipple discharge revealed clusters of glandular cells characterized by mild pleomorphic appearance and the presence of some nematodes of about 350 microm in length in the background. The smears also contained several inflammatory cells, including eosinophils. Both the Knott a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…However, despite the high frequency of mammary lesions in dogs, there is no report describing the use of this method for assessing mammary lesions. There is only one report describing the use of this technique in a case of dirofilariasis diagnosed by papillar discharge cytology in a bitch …”
Section: Discussionsupporting
confidence: 84%
“…However, despite the high frequency of mammary lesions in dogs, there is no report describing the use of this method for assessing mammary lesions. There is only one report describing the use of this technique in a case of dirofilariasis diagnosed by papillar discharge cytology in a bitch …”
Section: Discussionsupporting
confidence: 84%
“…Dirofilaria repens infection of the mammary gland in the bitch (Manuali et al, 2005), mycotic mastitis due to Blastomyces dermatitidis in three dogs (Ditmyer and Craig, 2011), and mastitis due to Toxoplasma gondii in a cat (Park et al, 2007) have been reported. Mastitis may infrequently occur from hematogenous spread of organisms, nonlactation-associated trauma, fight wounds, or infected neoplasms.…”
Section: Mammary Gland Inflammation/infectionmentioning
confidence: 99%
“…Presence of phagocytosis, degenerated neutrophils, macrophage-foamy cells, bacteria and erythrocytes on milk smears is consistent with a positive diagnostic for Mastitis acuta (Olson and Olson, 1984;Manuali et al, 2004;Sangha et al, 2011).…”
Section: Resultsmentioning
confidence: 53%